The award : a novel - Steel, Danielle; Verner, Adam (Grand Haven, Michigan : Brilliance Audio, 2016)
When Gaëlle de Barbet learns she will be receiving the Legion of Honor medal, she relives her past and must make peace with it in order to heal.
Read by Adam Verner.
Keywords: World War, 1939-1945 -- Underground movements -- France -- Fiction; World War, 1939-1945 -- Participation, Female -- Fiction; France -- History -- German occupation, 1940-1945 -- Fiction; Historical fiction; Audiobooks